Circulating tumor cell isolation for cancer diagnosis and prognosis - Zicheng Deng; Sheng‐Ming Wu; Yilong Wang; Donglu Shi (2022)
Circulating tumor cells (CTCs) are tumor cells that shed from the primary tumor and intravasate into the peripheral blood circulation system responsible for metastasis. Sensitive detection of CTCs from clinical samples can serve as an effective tool in cancer diagnosis and prognosis through liquid biopsy. Current CTC detection technologies mainly reply on the biomarker-mediated platforms including magnetic beads, microfluidic chips or size-sensitive microfiltration which can compromise detection sensitivity due to tumor heterogeneity. A more sensitive, biomarker independent CTCs isolation technique has been recently developed with the surface-charged superparamagnetic nanoprobe capable of different EMT subpopulation CTC capture from 1 mL clinical blood. In this review, this new strategy is compared with the conventional techniques on biomarker specificity, impact of protein corona, effect of glycolysis on cell surface charge, and accurate CTC identification. Correlations between CTC enumeration and molecular profiling in clinical blood and cancer prognosis are provided for clinical cancer management.